A Comparative Analysis of Students' Mathematics Metacognitive Awareness in the Medium of Instruction - Paudel, Krishna Chandra; Ghimire, Shree Prasad (Mathematics Education Forum Chitwan, 2025)
Metacognitive awareness has a decisive role in learning mathematics. This research has investigated the amount of metacognitive awareness in mathematics among secondary level students and examined variations in the language of instruction (English vs. Nepali). We were used a cross-sectional quantitative survey method for 402 students of grade IX and six schools from the Kathmandu district. The Junior Metacognitive Awareness Inventory (Jr MAI) tool by Sperling et al. (2002) was used by translating and modifying in the Nepalese context to evaluate metacognitive awareness. The quantitative data were analyzed by using SPSS 20 version with descriptive statistics and use independent samples t-test. The results revealed that students showed a relatively higher average metacognitive awareness, which is significantly higher. Students from Nepali medium schools achieved slightly higher scores (p = 0.237) than English medium schools, which is not significant at 0.05 level of significance. These results designated that the medium of instruction might not be an influential factor in the metacognitive development of students.